Stability in seed yield of french bean (Phaseolus vulgaris) genotypes in high-hill, dry temperate region of northwestern Himalayas - Panwar, K S; Chaudhari, H K; Thakur, S R (The Indian Journal of Agricultural Sciences, 2012)
A set of 24 genotypes of french bean (Phuseolus vulgaris L.) grown in 3 distinct environments (Sangla, Kukumseri and Leo) in dry temperate region for 2 years was studied for stability in yield. Stability performance analysis in 6 environments revealed significant differences due to genotypes, environments and genotypes x environment (G X E) interactions. Both linear and non-linear components of G x E interaction were present, with predominance of the former component. The genotypes showing wide adaptabIlity and specific adaptation were identified. ’KRC 5’. ’KRC 8’ and ’KRC 11’ were observed high yielding, out of which ’KRC 8’ proved widely adaptable.